Organogenesis de raices en geranio - Alva T, T.=700 1 oropeza C, M.; Vargas C, T.E.
(En, Es)
ilus., 5 ref.
Keywords: ORGANOGENESIS; CALLO; RAICES; CULTIVO IN VITRO; PELARGONIUM PELTATUM; VENEZUELA; AGRONOMIA TROPICAL